Periostitis ossificans (Garrè’s osteomyelitis) radiographic study of two cases - S. K. KANNAN, G. SANDHYA & R. SELVARANI (IAPD and Blackwell, 2006)
Periostitis ossificans (PO) is a type of chronic osteomyelitis, more popularly known as Garrè’s osteomyelitis.